دور الوسائط التشكيلية المستحدثة في تعزيز البعد التعبيري لعنصر العين كموضوع للمنسوجة اليدوية - الشوشاني، هبة رمضان عبدالحميد محمد (الجمعية العربية للحضارة والفنون الإسلامية, 2022)
إن الفنان في سعيه لاكتشاف رؤى جديدة في الفن لابد له من أن يغير نظرته للثوابت المتعارف عليها وأن يبحث عن كل ما هو جديد سواء في الخامة أو التقنية أو الموضوع. ومن هنا اتجهت الباحثة إلى محاولة التجريب بخامة مستحدثة ألا وهي راتنج الإيبوكسي. تلك الخامة المستخدمة حديثا في أعمال الديكور وبعض أنواع الحلي والتي تتميز بشفافية عالية وقوة التصاق ومظهر زجاجي لامع. ومن الاتجاهات التشكيلية ذلك الاتجاه الذي يتعامل فيه الفنان مع الموضوع باعتباره أحد المقومات الفكرية والتعبيرية للعمل الفني. ولقد وقع اختيار الباحثة على عيون المخلوقات كموضوع لتجربتها البحثية لتنوعها. وباعتبارها عناصر مليئة بالإيماءات التعبيرية والدلالات والمشاعر. ومن هنا تولدت مشكلة البحث في كيفية التعبير تشكيليا عن عيون المخلوقات بما تبثه من مشاعر وأحاسيس وانفعالات من خلال توظيف الوسائط التشكيلية المستحدثة كراتنج الإيبوكسي لتأكيد البعد التعبيري لعنصر العين في المنسوجة اليدوية. ويهدف البحث إلى الكشف عن الإمكانات التشكيلية والتعبيرية لبعض الخامات والوسائط المستحدثة وتوظيفها لتأكيد البعد التعبيري لعيون المخلوقات كموضوع المنسوجة اليدوية. ولتحقيق أهداف البحث قامت الباحثة بإنتاج مجموعة من النسجيات اليدوية التي تعبر عيون المخلوقات باستخدام الوسائط التشكيلية النسجية المستحدثة لتأكيد البعد التعبيري في موضوع المنسوجة. وقد اتجهت الباحثة إلى مدخلين في التجريب لتحديث المنسوجة اليدوية المعاصرة جماليا وتعبيريا هما الموضوع والوسائط التشكيلية. وأثبتت نتائج البحث صحة الفروض بإثراء البعد التعبيري للمنتج النسجي اليدوي من خلال الموضوع والوسائط التشكيلية المستخدمة من خامات وتقنيات ووسائط أخرى مساعدة. The artist on his pursuing to discover new artistic visions has to change his insight of customary parameters and to look for whatever is new weather in the material, technique or the subject. Accordingly, the researcher has tended to experiment innovative materiel, which is epoxy resins. This new innovative materiel in redecorating and some accessories is characterized by its high transparency, strength of adhesiveness and shiny glass appearance. One of the plastic arts trends is the artist dealing with the subject as one of the intellectual and expressive components of the artwork. Creatures' eyes was selected by the researcher as a subject for her research experiment due to its variety and being full of expressive gestures, connotations and emotions. Therefore, looking into how to express creatures' eyes in a plastic arts way was a problem, given how they disclose emotions and feelings through enrolling the innovative plastic arts modes such as epoxy resins to emphasize the expressive dimension of the eye element in the hand-woven textile. The research aims to reveal the plastic media and expressionist potentials of some materials and innovative modes and enrolling them to emphasize the expressive dimension of the creatures' eyes as the subject of the hand-woven. And to achieve the research objectives, the researcher produced a collection of hand-woven which expresses the creatures' eyes by using innovative plastic media textiles to emphasize the expressive dimension of the textile. The researcher has tended to experiment two directions to update the modern-day hand-woven aesthetically and expressively, which are; the subject and the plastic media modes. The research results has proved the validity of the assumptions by enhancing the expressive dimension of the hand-woven product through the used subject and plastic media modes such as materials, technique and other helpful modes.
Keywords: المنسوجات اليدوية -- الفنون التشكيلية -- حاسة البصر